Analysis of intermediate pressure SiH4/He capacitively coupled plasma for deposition of an amorphous hydrogenated silicon film in consideration of thermal diffusion effects. (17th July 2017) - Kim, Ho Jun; Lee, Hae June
Abstract: To achieve rapid, uniform deposition of an amorphous hydrogenated silicon (a-Si:H) film, a capacitively coupled plasma (CCP) is often used at an intermediate pressure (>100 Pa), with a silane (SiH4 )-based mixture. At these pressures, heavy particle interactions (such as ion–ion, ion–neutral, and neutral–neutral reactions) contribute significantly to the formation of precursor radicals. By adding a consideration of the thermal diffusion effects to the neutral transport equation, the chemical processes have been numerically analyzed with variation in the number fraction of SiH4 and electrode spacing using a two-dimensional fluid model of radio frequency discharges in a cylindrically symmetric CCP reactor. The non-uniformity of the deposition rate profiles increases consistently as electrode spacing increases, although the non-uniformity of the plasma parameters decreases with the increase of electrode spacing. The simulated deposition rate profiles match well with the experimental data for the change of electrode spacing. Based on the validation of our model, we propose predictive designs to potentially improve the reactor and process by modifying the thermal and electrical surface conditions.